Depositional Model for Turbidite Lobes in Complex Slope Settings Along Transform Margins: The Motta San Giovanni Formation (Miocene—Calabria, Italy) - Rohais, Sébastien; Bailleul, Julien; Brocheray, Sandra; Schmitz, Julien; Paron, Paolo; Kezirian, Francis; Barrier, Pascal (Frontiers in Earth Science, 2021)
Intraslope lobes, or perched lobes, are attracting scientific interest because they represent a key archive between the shelf and the deep basin plain when looking at a complete source-to-sink depositional system across a continental margin and can form significant offshore hydrocarbon plays. In this study, we focus on a detailed characterization of intraslope lobes of the Motta San Giovanni Formation (Miocene, Calabria), which were deposited in confined conditions during the Miocene along a transform margin. We determine the typical facies associations and stratigraphic architecture of these intraslope lobes using a 3D digital outcrop model resulting from a combined Uncrewed Aerial Vehicle (UAV) and walking acquisition, together with sedimentological logging and geological mapping. We propose recognition criteria for the identification of intraslope lobes, including facies and geometries, integrated within a depositional model. A comparison with other well-known intraslope and confined lobes, as well as basin floor lobes, is finally discussed, to highlight the peculiarities of intraslope lobes deposited along transform margins. The diagnostic depositional model for these types of intraslope lobes includes four main stages of evolution: 1) Stage 1—isolated detached lobe precursor in response to a flushed hydraulic jump, 2) Stage 2—prograding and aggrading lobe elements associated with a relatively stable and submerged hydraulic jump in the Channel-Lobe Transition Zone (CLTZ), 3) Stage 3—major bypass associated with lateral accretion and local aggradation interpreted as a renewal of a normal hydraulic jump in the CTLZ, and 4) Stage 4—erosion and bypass then abandonment. The development of intraslope lobes along active transform margins is allowed by tectonically induced slope segmentation and local confinement. In such a context, flow stripping and overspill processes occurred. Resulting lobes appear to be particularly small and relatively thin sandy deposits. They could be considered end-member in a lobe classification based on the Net-to-Gross content (high) and taking into account their thickness/width ratio (intermediate between 10:1 and 100:1 lines).